A cross-sectional survey of Indian orthopaedicians to understand the place in therapy for the latest soft gel formulation of etoricoxib - Karvir, Sagar; Jadhwar, Sameer S.; Mehta, Kapil Dev (International Journal of Research in Orthopaedics, 2022)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly prescribed for arthritis (RA), osteoarthritis (OA), low back pain (LBP) and other musculoskeletal disorders. Novel formulations such as soft gel formulations are being introduced for NSAIDs in place of the traditional tablet formulation. The objective of this study was to quantify orthopaedicians insights for the recently available soft gel formulation of Etoricoxib. Methods: The questions for the survey instrument (Google forms) were developed by researchers upon review of scientific literature and subsequent discussions with practicing orthopaedicians. This was a cross-sectional digital survey involving 506 orthopaedicians across India via online responses collated via Google forms. Results: 81.4% doctors agreed that etoricoxib soft gel capsules are faster acting than the tablet formulation, whereas 89.6% of the doctors agree/strongly agreed that etoricoxib soft gel capsules would have better compliance because of its bitter taste masking ability. More than 96% doctors acknowledged that etoricoxib soft gel capsule’s characteristics such as higher drug dissolution and absorption would benefit their patients more than the etoricoxib tablet formulation. Conclusions: Given its advantages, the etoricoxib soft gel formulation, in the days to come, could be one of the preferred options for the management of pain and other arthritic conditions for patients in India.